Circadian Variation of Blood Pressure Is Impaired in Normotensive Pregnant Women with Gestational Diabetes Mellitus. (April 2013) - Soydinc, Hatice Ender; Davutoglu, Vedat; Sak, Muhammet Erdal; Ercan, Suleyman; Evsen, Mehmet Sıddık; Kaya, Hasan; Oylumlu, Muhammed; Buyukaslan, Hasan; Sari, Ibrahim
<x xml:space="preserve">Abstract</x> Data about circadian blood pressure (BP) in normotensive patients with gestational diabetes mellitus (GDM) are lacking. Thus, we sought to compare dipper and nondipper circadian variation of BP profile between normotensive women complicated with GDM and normal pregnant women. Forty-two women with GDM and 33 normal uncomplicated pregnant women who met the entry criteria for the study were enrolled in the study. Twenty-four-hour noninvasive ambulatory blood pressure monitoring and echocardiography to measure the left ventricle mass index and diastolic parameters were performed. Nocturnal blood pressure dipping was calculated as follows: (awake BP – sleep BP) × 100/awake BP. Patients with a nocturnal reduction in average daytime systolic BP and diastolic BP of less than 10% were classified as nondippers. Left ventricle mass index was higher in normotensive pregnant women with GDM group than in normal pregnant subjects (101.98 ± 24 g/m2 vs. 90.67 ± 15 g/m2, P < .018). Significant nocturnal systolic and diastolic nondippings were observed in GDM groups compared with normal subjects. From diastolic variables, the mitral E velocity and isovolumetric relaxation time were compatible with diastolic dysfunction relaxation abnormalities (P = .003 and P = .015, respectively) in nondipper group. From all confounding factors, only E velocity (P = .002) and diagnosis of GDM (P < .001) were predictive of nondipper circadian variation. This study shows that (i) circadian BP is impaired in normotensive pregnant subjects with GDM, (ii) the left ventricle mass index is higher in pregnant subjects with GDM than in normal pregnant subjects who despite a 24-hour BP are within normal limits, and (iii) in nocturnal nondipper group, the tendency to having diastolic relaxation abnormalities is noted.